2011
DOI: 10.1016/j.cplett.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of carbon nanotubes, fullerene and graphite under spark plasma sintering

Abstract: a b s t r a c tThe thermal stabilities of carbon nanotubes, fullerene and graphite were investigated under spark plasma sintering (SPS). Results were compared with data from synchrotron radiation in situ high temperature X-ray diffraction of these materials. Part of the nanotubes and fullerene transformed into diamond under SPS, but graphite kept stable. There was no diamond conversion in the in situ X-ray diffraction experiments under the same condition. Their phase transitional mechanism indicated the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 17 publications
(19 reference statements)
2
18
1
Order By: Relevance
“…After SPS processing, the MWCNTs diffraction peaks are still present in the sintered MWCNTs compacts, but the peaks of the CNTs (002), (100) and (004) are stronger than those in the raw MWCNTs. It indicates that the SPS process improved the crystallinity of the MWCNTs (Zhang, Mihoc et al, 2011). Additionally, new peaks were detected in the sample centered at 2.05, 1.23, 1.06 and 1.76 Å corresponding to the cubic diamond (ICDD No.…”
Section: Stability and Phase Transformation Of Carbon Materials Undermentioning
confidence: 87%
See 2 more Smart Citations
“…After SPS processing, the MWCNTs diffraction peaks are still present in the sintered MWCNTs compacts, but the peaks of the CNTs (002), (100) and (004) are stronger than those in the raw MWCNTs. It indicates that the SPS process improved the crystallinity of the MWCNTs (Zhang, Mihoc et al, 2011). Additionally, new peaks were detected in the sample centered at 2.05, 1.23, 1.06 and 1.76 Å corresponding to the cubic diamond (ICDD No.…”
Section: Stability and Phase Transformation Of Carbon Materials Undermentioning
confidence: 87%
“…The n-diamond is a new kind of carbon allotrope, which is a metallic form of carbon with face-centred cubic structure. It is a metastable and intermediate phase, can decompose slowly at room temperature, and has been synthesized accidentally by various processes (Zhang, Mihoc et al, 2011). It is noted that the n-diamond can also be synthesized by the SPS process.…”
Section: Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our researches have shown that carbon nanotubes are unstable and can be converted into diamond without [8][9][10] or with metallic catalysts [11] under the pulsed electric field of the SPS. Our recent work has shown that C60 can be converted into diamond under the same SPS conditions as carbon nanotubes are converted to diamond (1500 1C, 80 MPa) [12]. Since the C60 has a higher sp 3 hybridization fraction than that of carbon nanotubes, it makes the transformation of C60 into diamond easier.…”
Section: Introductionmentioning
confidence: 98%
“…[127] In summary, CNTs may transform into other thermodynamically stable allotropes during the heat treatment process. Among these allotropes, cubic diamond [105], n-diamond [122], mono/multi-layer graphene [106], and graphite sheets [107] are the most extensively reported. However, the way these allotropes can affect the final properties are highly contradictory.…”
Section: Thermal Decomposition Of Pure Cntsmentioning
confidence: 99%